First cosmic-ray images of bone and soft tissue. (28th December 2016) - Mrdja, Dusan; Bikit, Istvan; Bikit, Kristina; Slivka, Jaroslav; Hansman, Jan; Oláh, László; Varga, Dezső
Abstract: More than 120 years after Roentgen's first X-ray image, the first cosmic-ray muon images of bone and soft tissue are created. The pictures, shown in the present paper, represent the first radiographies of structures of organic origin ever recorded by cosmic rays. This result is achieved by a uniquely designed, simple and versatile cosmic-ray muon-imaging system, which consists of four plastic scintillation detectors and a muon tracker. This system does not use scattering or absorption of muons in order to deduct image information, but takes advantage of the production rate of secondaries in the target materials, detected in coincidence with muons. The 2D image slices of cow femur bone are obtained at several depths along the bone axis, together with the corresponding 3D image. Real organic soft tissue, polymethyl methacrylate and water, never seen before by any other muon imaging techniques, are also registered in the images. Thus, similar imaging systems, placed around structures of organic or inorganic origin, can be used for tomographic imaging using only the omnipresent cosmic radiation.